Polymeric-Coated Monoammonium Phosphate with Different Release Profiles for Improving Phosphorus Use Efficiency in Forage Production - Costa, Cibeli L.; Bortoletto-Santos, Ricardo [UNESP]; Mitsuyuki, Milene C.; Ribeiro, Caue; Bernardi, Alberto; Nogueira, Ana Rita A. (American Chemical Society (ACS), 2024)
As one of the essential nutrients plants need to grow, phosphorus presents the drawback of immobilizing in high-Fe and Al soils. Therefore, it is necessary to properly manage P-containing fertilizers to optimize the crop nutrient amount and synchronize their plant uptake with the release of nutritional composition. Coated fertilizers can improve the availability of nutrients by reducing losses due to fixation or leaching. The present study investigated the effects of monoammonium phosphate (MAP) granules coated with a green and biodegradable castor oil-based polyurethane layer film (2 to 8% by weight) on plant development and P absorption. A greenhouse experiment with two crops as the test plants was performed. The study found a well-adjusted nutrition profile in both cultures with a continuous nutrient supply when mixing the different MAP-coated granules. Combining particles with different release rates can balance the slow-release effect of coating and nutrient absorption by plants, thereby allowing for a continuous nutrient supply from a single fertilization. Our results can support the design of more efficient controlled-released systems, providing a new approach to reducing the application and increasing the efficiency of phosphorus fertilizer. The presence of a coating improves the nutrient absorption of plants. At the same time, the coating used has good biocompatibility.
Keywords: castor oil; fertilizer; nutrient controlled release; palisade grass; ryegrass